Two-dimensional vermiculite / MXene ceramic composite membrane for organic solvent nanofiltration and preparation method of two-dimensional vermiculite / MXene ceramic composite membrane

By combining two-dimensional vermiculite with MXene and calcining at low temperature on the inner wall surface of the α-Al2O3 ceramic membrane tube, the problems of insufficient corrosion resistance of traditional organic membrane materials and complex and high cost of ceramic nanofiltration membrane preparation process are solved, and a high-performance ceramic composite membrane material is realized, suitable for organic solvent nanofiltration.

CN119896981APending Publication Date: 2025-04-29NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510102740.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional organic membrane materials have insufficient corrosion resistance, and the preparation process of traditional ceramic nanofiltration membranes is complex and costly.

Method used

Two-dimensional vermiculite was compounded with MXene, deposited on the inner wall surface of the α-Al2O3 ceramic membrane tube, and a nurse filter-grade ceramic separation membrane was prepared by low-temperature calcination.

Benefits of technology

It significantly improves the mechanical strength and flexibility of the composite membrane, achieves excellent performance of hardness and flexibility, has good chemical stability and separation characteristics, and is suitable for organic solvent nanofiltration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896981A_ABST
    Figure CN119896981A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional vermiculite / MXene ceramic composite membrane for organic solvent nanofiltration and a preparation method thereof.The preparation method comprises the steps that a single-channel tubular alpha-Al2O3 ceramic membrane serves as a supporting body, two-dimensional vermiculite / MXene composite nanosheets are assembled to the alpha-Al2O3 supporting body in a pressure-assisted deposition mode, then low-temperature calcination is conducted, and the two-dimensional vermiculite / MXene ceramic composite membrane is prepared. The two-dimensional vermiculite / MXene ceramic composite membrane prepared by the invention is simple in preparation process, the support layer and the separation layer show good bonding performance and excellent permeation flux, and when the two-dimensional vermiculite / MXene ceramic composite membrane is applied to cross-flow filtration of an ethanol solvent / methylene blue dye, excellent ethanol permeation flux is shown while a high rejection rate of methylene blue is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material science and membrane separation technology, and in particular to a ceramic composite membrane material obtained by compounding two-dimensional vermiculite with MXene and calcining the composite membrane material on the inner wall surface of an α-Al2O3 ceramic membrane tube at a low temperature. Background Art

[0002] Membrane separation technology has important applications in the fields of chemical industry, environmental protection and energy. Organic solvent nanofiltration membrane separation technology uses precise nanofiltration membranes to finely filter organic solvents, thereby effectively removing impurities and obtaining high-purity products. Common organic solvent nanofiltration membranes are polymer membranes, which have good ductility and easy processing, but their temperature resistance and chemical resistance are insufficient and cannot meet the requirements of harsh working conditions. Inorganic ceramic membranes have excellent mechanical strength and high temperature and corrosion resistance, but nanofiltration-grade ceramic membranes usually require layer-by-layer transition sintering preparation, which has a complex preparation process and high production cost. Therefore, the development of low-cost, high-performance ceramic membrane materials is an important direction for organic solvent nanofiltration technology.

[0003] Two-dimensional vermiculite is a layered silicate material with high mechanical strength and excellent chemical stability. Its excellent ceramic properties make it possible to construct two-dimensional ceramic separation membranes. MXene, as a two-dimensional ceramic material, has good flexibility and has been widely used in the construction of two-dimensional separation membrane materials. On the other hand, MXene, as a ceramic sintering aid, can significantly improve the toughness and interfacial bonding strength of ceramic materials. The composite of two-dimensional vermiculite and two-dimensional MXene can effectively construct a membrane material separation layer with precise mass transfer channels. The calcined two-dimensional vermiculite / MXene separation membrane has a solid ceramic structure and exhibits excellent molecular sieving and chemical corrosion resistance.

[0004] The present invention deposits a two-dimensional vermiculite and MXene composite material on the inner wall surface of an α-Al2O3 ceramic membrane tube and adopts a low-temperature calcination process, which significantly reduces the energy consumption of preparation while maintaining the microstructural integrity and chemical stability of the material. Combining the rigidity of two-dimensional vermiculite, the toughening of two-dimensional MXene, and the high-strength support of the α-Al2O3 ceramic membrane tube, the prepared ceramic composite membrane material exhibits excellent corrosion resistance and separation performance, and can be applied to organic solvent nanofiltration to meet the use requirements in harsh environments. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of insufficient corrosion resistance of traditional organic membrane materials and complex and high cost of traditional ceramic nanofiltration membranes. A two-dimensional vermiculite / MXene ceramic composite membrane for organic solvent nanofiltration and a preparation method thereof are provided. By compounding two-dimensional vermiculite and MXene, depositing them on the inner wall surface of an α-Al2O3 ceramic membrane tube, and calcining at low temperature, a nanofiltration-grade ceramic separation membrane is successfully prepared, which significantly simplifies the preparation process and cost of the ceramic nanofiltration membrane.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0007] The two-dimensional vermiculite / MXene ceramic composite membrane for organic solvent nanofiltration of the present invention comprises a single-channel α-Al2O3 ceramic membrane support and a two-dimensional vermiculite / MXene separation layer on the surface; the bonding between the support and the separation layer is increased by low-temperature calcination, wherein the support is a single-channel tubular α-Al2O3 membrane with an average pore size of 100-300nm, and the separation layer is a two-dimensional vermiculite / MXene composite nanosheet laminated structure with a sheet diameter of 5-8μm.

[0008] The present invention provides a method for preparing a two-dimensional vermiculite / MXene ceramic composite membrane for organic solvent nanofiltration, and the preparation method comprises the following steps:

[0009] 1) Preparation of MXene nanosheets: Lithium fluoride (LiF) was weighed and added to a 9 mol / L hydrochloric acid solution, and stirred at room temperature to obtain a uniform mixed solution; Ti3AlC2 was then slowly added to the mixed solution, and stirred at 40°C for 24 h to complete the etching reaction; the obtained mixture was washed and ultrasonically treated until the pH value of the supernatant was 7; the mixed solution was diluted and ultrasonicated for 60 min, and centrifuged for 30 min, and the supernatant was collected as the MXene solution; finally, the solution was sealed and refrigerated for storage under nitrogen protection;

[0010] 2) Preparation of vermiculite solution: The heat-expanded vermiculite powder was immersed in a saturated sodium chloride (NaCl) solution and heated under stirring and reflux at 120°C for 24 h; after centrifugation, the supernatant was discarded and repeatedly washed until no chloride ions could be detected in the supernatant, and finally the precipitate Na + -Vermiculite; Na + - Vermiculite was further dispersed in lithium chloride (LiCl) solution, heated under reflux with stirring at 120 °C for 24 h, and the washing process was repeated to obtain Li + -vermiculite; after centrifugation, rinse thoroughly with deionized water, disperse the obtained product in a hydrogen peroxide (H2O2) solution, and reflux heat at 120°C for 24h; finally, repeat the washing process again to obtain a dispersion having a single layer of vermiculite nanosheets;

[0011] 3) Preparation of vermiculite / MXene composite material: The prepared MXene nanosheets and vermiculite solution are dispersed in water in a certain proportion, and ultrasonically homogenized to obtain a two-dimensional vermiculite / MXene composite nanosheet solution;

[0012] 4) assembling the two-dimensional vermiculite / MXene composite nanosheets onto the α-Al2O3 ceramic membrane support using a homemade pressure-assisted deposition method and drying them naturally at room temperature;

[0013] 5) The dried α-Al2O3 ceramic membrane-supported two-dimensional vermiculite / MXene composite membrane is placed in a muffle furnace for low-temperature calcination to obtain a two-dimensional vermiculite / MXene ceramic composite membrane.

[0014] The assembly pressure of the two-dimensional vermiculite / MXene composite nanosheets in step 4) is 0.1-0.3 MPa.

[0015] In the step 5), low temperature calcination is performed at room temperature at a heating rate of 2-5°C / min to 200-600°C, and the temperature is kept for 24 hours, and finally naturally cooled to room temperature.

[0016] The beneficial effect of the present invention is that by low-temperature calcining the two-dimensional vermiculite and MXene composite material on the surface of the α-Al2O3 ceramic membrane tube, the mechanical strength and flexibility of the composite membrane are significantly improved, and the excellent performance of rigid-flexible synergy is achieved. Vermiculite provides rigidity, MXene enhances mechanical strength and separation performance, and the two-dimensional vermiculite / MXene separation layer calcined at low temperature exhibits good chemical stability and separation characteristics, so that the composite membrane can adapt to the organic solvent environment for a long time. The high-strength support of the α-Al2O3 ceramic membrane tube further improves the stability of the membrane structure. In addition, the low-temperature calcination process not only saves energy consumption, but also ensures the integrity of the material microstructure, so that the composite membrane has excellent performance in separation efficiency, chemical tolerance and service life, and is suitable for complex working conditions such as organic solvent nanofiltration. Compared with traditional ceramic membranes, the composite membrane of the present invention has lower preparation energy consumption and a wider range of applicable environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the structure of the two-dimensional vermiculite / MXene ceramic composite membrane ceramic composite nanofiltration membrane prepared in Example 1;

[0018] Figure 2 This is a transmission electron microscopy image of the two-dimensional vermiculite / MXene composite nanosheet prepared in Example 1;

[0019] Figure 3 This is a scanning electron microscope image of the two-dimensional vermiculite / MXene ceramic composite membrane ceramic composite nanofiltration membrane prepared in Example 2.

[0020] In the figure: support body 1, separation layer 2. DETAILED DESCRIPTION

[0021] The present invention will be further described in detail below with reference to specific embodiments, but the present invention is not limited thereto.

[0022] Example 1

[0023] A method for preparing a high permeation flux two-dimensional vermiculite / MXene ceramic composite nanofiltration membrane for organic solvent nanofiltration comprises the following steps:

[0024] (1) Preparation of MXene nanosheets: Lithium fluoride (LiF) was weighed and added to a 9 mol / L hydrochloric acid solution, and stirred at room temperature to obtain a uniform mixed solution; Ti3AlC2 was then slowly added to the mixed solution, and stirred at 40°C for 24 h to complete the etching reaction; the resulting mixture was washed and ultrasonically treated until the pH value of the supernatant reached 7; the mixed solution was diluted and ultrasonicated for 60 min, and centrifuged for 30 min, and the supernatant was collected as the MXene solution; finally, the solution was sealed and refrigerated for storage under nitrogen protection;

[0025] (2) Preparation of vermiculite solution: The heat-expanded vermiculite powder was immersed in a saturated sodium chloride (NaCl) solution and heated under reflux at 120°C for 24 h. After centrifugation, the supernatant was discarded and the solution was repeatedly washed until no chloride ions were detected in the supernatant. Finally, the precipitate Na + -Vermiculite; Na + - Vermiculite was further dispersed in lithium chloride (LiCl) solution, heated under reflux with stirring at 120 °C for 24 h, and the washing process was repeated to obtain Li + -vermiculite; after centrifugation, thoroughly rinse with deionized water, disperse the obtained product in a hydrogen peroxide (H2O2) solution, and reflux and heat at 120°C for 24h; finally, repeat the washing process again to obtain a dispersion having a single layer of vermiculite nanosheets;

[0026] (3) Preparation of two-dimensional vermiculite / MXene composite materials and assembly of α-Al2O3 ceramic support: Vermiculite and MXene solution (1:1) were mixed and stirred at room temperature for 12 h to obtain a uniformly dispersed vermiculite / MXene composite nanosheet solution. The composite solution was loaded onto the inner wall of an α-Al2O3 ceramic membrane tube with a pore size of 200 nm using a pressure-assisted deposition device, with a controlled pressure of 0.1 MPa and a loading of 12 mg. The assembled composite membrane was naturally dried at room temperature for 24 h.

[0027] (4) Low-temperature calcination of the two-dimensional vermiculite / MXene ceramic composite nanofiltration membrane: The dried composite membrane was placed in a muffle furnace for low-temperature calcination. The low-temperature calcination procedure was as follows: heating to 200 °C at a heating rate of 2 °C / min, keeping warm for 24 h, and naturally cooling to room temperature.

[0028] The two-dimensional vermiculite / MXene composite ceramic nanofiltration membrane of this embodiment has a retention rate of 99% for methylene blue in ethanol solution under cross-flow filtration, and a permeation flux of 1280.23 L·m -2 ·h -1 bar -1 .

[0029] Example 2

[0030] (1) Preparation of MXene nanosheets: Lithium fluoride (LiF) was weighed and added to a 9 mol / L hydrochloric acid solution, and stirred at room temperature to obtain a uniform mixed solution; Ti3AlC2 was then slowly added to the mixed solution, and stirred at 40°C for 24 h to complete the etching reaction; the resulting mixture was washed and ultrasonically treated until the pH value of the supernatant reached 7; the mixed solution was diluted and ultrasonicated for 60 min, and centrifuged for 30 min, and the supernatant was collected as the MXene solution; finally, the solution was sealed and refrigerated for storage under nitrogen protection;

[0031] (2) Preparation of vermiculite solution: The heat-expanded vermiculite powder was immersed in a saturated sodium chloride (NaCl) solution and heated under reflux at 120°C for 24 h. After centrifugation, the supernatant was discarded and the solution was repeatedly washed until no chloride ions were detected in the supernatant. Finally, the precipitate Na + -Vermiculite; Na + - Vermiculite was further dispersed in lithium chloride (LiCl) solution, heated under reflux with stirring at 120 °C for 24 h, and the washing process was repeated to obtain Li + -vermiculite; after centrifugation, thoroughly rinse with deionized water, disperse the obtained product in a hydrogen peroxide (H2O2) solution, and reflux and heat at 120°C for 24h; finally, repeat the washing process again to obtain a dispersion having a single layer of vermiculite nanosheets;

[0032] (3) Preparation of two-dimensional vermiculite / MXene composite materials and assembly of α-Al2O3 ceramic support: Vermiculite and MXene solution (1:3) were mixed and stirred at room temperature for 12 h to obtain a uniformly dispersed vermiculite / MXene composite nanosheet solution. The composite solution was loaded onto the inner wall of an α-Al2O3 ceramic membrane tube with a pore size of 200 nm using a pressure-assisted deposition device, with a controlled pressure of 0.1 MPa and a loading of 12 mg. The assembled composite membrane was naturally dried at room temperature for 24 h.

[0033] (4) Low-temperature calcination of the two-dimensional vermiculite / MXene ceramic composite nanofiltration membrane: The dried composite membrane was placed in a muffle furnace for low-temperature calcination. The low-temperature calcination procedure was as follows: heating to 600 °C at a heating rate of 2 °C / min, keeping warm for 24 h, and naturally cooling to room temperature.

[0034] The two-dimensional vermiculite / MXene ceramic composite nanofiltration membrane of this embodiment exhibited excellent organic solvent nanofiltration performance under cross-flow filtration, with a retention rate of 99% for methylene blue in ethanol solution and a permeation flux of 1553.05 L·m -2 ·h -1 bar -1 The two-dimensional vermiculite and MXene composite material of the present invention is successfully constructed on the inner wall surface of an α-Al2O3 ceramic tube with a pore size of 200 nm through low-temperature calcination, has excellent separation performance and chemical stability, and can be applied to the field of nanofiltration separation under harsh environments.

Claims

1. A two-dimensional vermiculite / MXene ceramic composite membrane for organic solvent nanofiltration, characterized in that: The invention comprises a single-channel α-Al2O3 ceramic membrane support (1) and a two-dimensional vermiculite / MXene separation layer (2) on the surface; the bonding between the support (1) and the separation layer (2) is increased by low-temperature calcination, wherein the support (1) is a single-channel tubular α-Al2O3 membrane with an average pore size of 100-300nm, and the separation layer (2) is a two-dimensional vermiculite / MXene composite nanosheet laminate structure with a sheet size of 5-8μm.

2. The method for preparing a two-dimensional vermiculite / MXene ceramic composite membrane for organic solvent nanofiltration according to claim 1, characterized in that: The specific steps include: 1) Preparation of MXene nanosheets: Lithium fluoride (LiF) was weighed and added to a 9 mol / L hydrochloric acid solution, and stirred at room temperature to obtain a uniform mixed solution; Ti3AlC2 was then slowly added to the mixed solution, and stirred at 40°C for 24 h to complete the etching reaction; the obtained mixture was washed and ultrasonically treated until the pH value of the supernatant was 7; the mixed solution was diluted and ultrasonicated for 60 min, and centrifuged for 30 min, and the supernatant was collected as the MXene solution; finally, the solution was sealed and refrigerated for storage under nitrogen protection; 2) Preparation of vermiculite solution: Immerse the heat-expanded vermiculite powder in a saturated sodium chloride (NaCl) solution and heat under reflux at 120° C. for 24 h; After centrifugation, the supernatant was discarded and washed repeatedly until no chloride ions could be detected in the supernatant, and finally the precipitate Na + -Vermiculite; Na + - Vermiculite was further dispersed in lithium chloride (LiCl) solution, heated under reflux with stirring at 120 °C for 24 h, and the washing process was repeated to obtain Li + -vermiculite; after centrifugation, thoroughly rinse with deionized water, disperse the obtained product in a hydrogen peroxide (H2O2) solution, and reflux and heat at 120°C for 24h; finally, repeat the washing process again to obtain a dispersion having a single layer of vermiculite nanosheets; 3) Preparation of vermiculite / MXene composite material: The prepared MXene nanosheets and vermiculite solution are dispersed in water in a certain proportion, and ultrasonically homogenized to form a two-dimensional vermiculite / MXene composite nanosheet solution; 4) assembling the two-dimensional vermiculite / MXene composite nanosheets onto the α-Al2O3 ceramic membrane support using a homemade pressure-assisted deposition method and drying them naturally at room temperature; 5) The dried α-Al2O3 ceramic membrane-supported two-dimensional vermiculite / MXene composite membrane is placed in a muffle furnace for low-temperature calcination to obtain a two-dimensional vermiculite / MXene ceramic composite membrane.

3. The preparation method according to claim 2, characterized in that: The assembly pressure of the two-dimensional vermiculite / MXene composite nanosheets in step 4) is 0.1-0.3 MPa.

4. The method for preparing a two-dimensional vermiculite / MXene ceramic composite membrane according to claim 2, characterized in that: In the step 5), low-temperature calcination is performed at room temperature at a heating rate of 2-5°C / min to 200-600°C, and the temperature is kept at this temperature for 24 hours, and finally the calcination is naturally cooled to room temperature.